2019
DOI: 10.1038/s41598-019-46195-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognosis markers for endometrial cancer by integrated analysis of DNA methylation and RNA-Seq data

Abstract: Endometrial cancer is highly malignant and has a poor prognosis in the advanced stage, thus, prediction of its prognosis is important. DNA methylation has rapidly gained clinical attention as a biomarker for diagnostic, prognostic and predictive purposes in various cancers. In present study, differentially methylated positions and differentially expressed genes were identified according to DNA methylation and RNA-Seq data. Functional analyses and interaction network were performed to identify hub genes, and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…This further reinforces the fundamental involvement of TTAGPs in cellular division. Our findings are further validated by the identification of hub genes CCNA2, CDK1, AURKA and CCNB1 in the network of DEGs between EC and normal tissue, which are consistent with previous studies [ 118 , 119 , 120 , 121 , 122 ]. Therefore, it is not surprising that many of the identified hub genes have already been implicated in EC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This further reinforces the fundamental involvement of TTAGPs in cellular division. Our findings are further validated by the identification of hub genes CCNA2, CDK1, AURKA and CCNB1 in the network of DEGs between EC and normal tissue, which are consistent with previous studies [ 118 , 119 , 120 , 121 , 122 ]. Therefore, it is not surprising that many of the identified hub genes have already been implicated in EC.…”
Section: Discussionsupporting
confidence: 92%
“…EZH2 has been reported to interact with TERF2 and TERF2IP [ 131 ], of the shelterin complex, and also telomeric repeat-containing RNA ( TERRA ) [ 132 , 133 ]. In our survival analysis, AURKA and CCNA2 were identified as markers of unfavourable prognosis ( Table S34 ), which is supported by previous immunohistochemical studies [ 122 , 134 ]. Polymorphisms within the RAD51 gene have been associated with EC progression and recurrence [ 135 , 136 ].…”
Section: Discussionsupporting
confidence: 87%
“…CDC20, in cooperation with other factors, has been reported to be an important modulator of the cell cycle and is associated with advanced tumor stages and higher grades in multiple cancer types, including pancreatic (58), breast (59) and colorectal cancer (60). A previous study suggested that low CDC20 expression is associated with an improved OS rate and that knockdown of CDC20 expression suppresses proliferation of EC cells (61).…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic profile of tumor epithelial cells and their associated microenvironment are currently being explored in other tumor models such as prostate and breast cancer [18,19]. Although the epigenetic landscape has been investigated in endometrial cancer [20][21][22][23][24], there is limited analysis independently examining epithelial and stromal compartments.…”
Section: Introductionmentioning
confidence: 99%